A hybrid Christian identity in Philippians 1:15–18 - Lee, Woo Min (HTS teologiese studies, 2021)
There have been various studies on the passage of Philippians 1:15–18 but there have been few studies on a hybrid aspect of Christian identity implicated in the passage. The aim of the study was to reveal a hybrid aspect of the passage. The socio-historical setting for the study was the Greco-Roman period. For this study, I employed rhetorical criticism, a socio-linguistic approach and an anthropological linguistic approach to the passage, as well as the analysis of the socio-historical and cultural background of the passage. As a result, I found that Paul, who retained his Jewish identity but embraced Christian identity, tried to suggest such a new kind of identity for the intended audience and their community. In this article, I argued that Paul as a hybrid personality urged the Christian community in Philippi to have distinguished Christian habitus and field in Philippians 1:15–18. In particular, Paul persuaded his intended audience or readers to acknowledge and accept even those preachers who had questionable intentions into their Christian community. Such an inclusive attitude was to make a clear distinction between the community and their traditional Greco-Roman socio-cultural background.Contribution: The research on Philippians 1:15–18 reveals a hybrid aspect of Christian identity implicated in the passage. This research would contribute to the biblical studies of the Hervormde Teologiese Studies journal through its rhetorical, socio-linguistic and anthropological approach to the biblical passage of Philippians 1:15–18.